1986
DOI: 10.18785/negs.0802.01
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of Spanish Mackerel, Scomberomorus maculatus, from the Southeastern United States

Abstract: Spanish mackerel, Scomberomorus maculatus, were collected during 1977·80 in the Gulf of Mexico and from North Carolina to south Florida during 1980·81 to describe their reproductive biology. The major spawning period extended from May to September in all areas and peaked during the spring and early summer. Most fish were mature at about 350 mm FL, but size at maturity varied between sexes and sampling areas. Males matured at a smaller size than females. Fecundity was estimated from 52 fish from all areas and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…An extensive period of growth band formation was found in adults, suggesting that there may also be a strong influence of reproduction activity, promoting a redirection of energy to gonad maturity and reproduction, with a consequent reduction in somatic growth and possibly leading to the formation of translucent bands. In northeastern Brazil, S. cavalla exhibits full spawning, which is more intense between September and March (FONTELES-FILHO, 1988), coinciding with the period of smaller marginal increments, as observed in the otoliths of adult specimens in the present study. Ximenes et al (1978) found similar results in northeastern Brazil, with reductions in the translucent margins occurring in the otoliths from December to March, corresponding to the period of intense reproduction (GESTEIRA;MESQUITA, 1976).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…An extensive period of growth band formation was found in adults, suggesting that there may also be a strong influence of reproduction activity, promoting a redirection of energy to gonad maturity and reproduction, with a consequent reduction in somatic growth and possibly leading to the formation of translucent bands. In northeastern Brazil, S. cavalla exhibits full spawning, which is more intense between September and March (FONTELES-FILHO, 1988), coinciding with the period of smaller marginal increments, as observed in the otoliths of adult specimens in the present study. Ximenes et al (1978) found similar results in northeastern Brazil, with reductions in the translucent margins occurring in the otoliths from December to March, corresponding to the period of intense reproduction (GESTEIRA;MESQUITA, 1976).…”
Section: Discussionsupporting
confidence: 82%
“…At ages of first sexual maturity, females begin to have larges sizes than males for the same age and reach larger asymptotic sizes (Table 3- Figure 8). Off the coast of Ceará, greater growth rates for females beginning in the adult phase stem from their greater voracity -as determined though studies on feeding habits (FONTELES-FILHO, 1988) -which may explain the inversion in growth rates found in the present study beginning in the adult phase.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations